دراسة تأثير مطروحات محطة الطاقة الكهربائية الحرارية في تراكيز بعض العناصر النزرة في مياه ورواسب نهر الفرات قرب مركز مدينة الناصرية-جنوب العراق - الخفاجي, باسم يوسف (University of Thi-Qar Journal of Science, 2014)
The present study was conducted to indicate effects of the Nassyria Thermal energy power plant on Euphrates river in Nassyria city - south Iraq, in four selected stations along a distance of 10 Km with in Euphrates river during the period Autumn 2010 to summer 2011. The investigation included the physical and chemical properties of water as well as concentration and distribution of some trace elements( Cd, Co, Fe, Ni, Pb, and Zn) in both dissolved and particulate phase for the water and sediments, Moreover , sediment texture and total organic carbon (TOC%) were also investigated. This study showed that the concentrations averages of Cd, Co, Fe, Ni, Pb and Zn in dissolved phase in water were (2.22 , 5.55 , 125.9 , 7.21 , 22 , and 10.03) μg/L respectively, while their concentrations in particulate phase were (16.67, 106.22 , 8496 , 146.43 , 1608.46 , and , 625.3) μg/g dry weight respectively. In sediments, the concentrations averages of trace elements they were (7, 30.76, 1633.75, 78.1, 192.75 , and 135.88) μg/g dry weight respectively. The statistical analysis didn't show a significant correlation between to most element in sediment and sediment texture in addition total organic carbon. Trace elements recorded were varied seasonally. The highest concentration among trace element was Fe and lowest concentration was Cd in both water phase and sediments, and the present study recoded value of trace elements in: particulate phase < sediment < dissolve phase.